Financial Development, Institutions, Growth and Poverty Reduction 2008
DOI: 10.1057/9780230594029_4
|View full text |Cite
|
Sign up to set email alerts
|

Finance and Poverty in Ethiopia: A Household-Level Analysis

Abstract: In this paper, using the rich household panel data of urban and rural Ethiopia that covers the period from 1994 to 2000, we attempted to establish the link between finance and poverty in Ethiopia. Our results show that access to finance is an important factor in consumption smoothing and hence poverty reduction. We also found evidence for a poverty trap due to liquidity constraints that limits the ability of the rural households from consumption smoothing. The empirical findings from this study could inform fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 27 publications
2
32
0
3
Order By: Relevance
“…Fouareg and Layte (2003), in their research exhibited that education level and the numbers of household members were effective on poverty. Geda et al (2001), in their study about absolute poverty in Kenya, found that the residence, gender, the sector of employment of the head of household, education level and household size affected poverty. Most of the studies about poverty in Albania rely on the expenditure and consumption data and thus use the poverty line computed from the Albania Living Standards Surveys data using the cost of basic needs method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Fouareg and Layte (2003), in their research exhibited that education level and the numbers of household members were effective on poverty. Geda et al (2001), in their study about absolute poverty in Kenya, found that the residence, gender, the sector of employment of the head of household, education level and household size affected poverty. Most of the studies about poverty in Albania rely on the expenditure and consumption data and thus use the poverty line computed from the Albania Living Standards Surveys data using the cost of basic needs method.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Matita and Chirwa [24] analyzed the extent of urban-rural welfare inequalities in Malawi with the help of a representative sample at the national level as well as the factors which contribute to such inequalities, using the decomposition techniques of both Oaxaca-Blinder [25,26] and Machado and Mata [27] The decomposition results of this study notably show that a large share of the welfare gap may be explained by the differences in the characteristics «physical assets and education» rather than by discrimination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This objective has been achieved in two stages: firstly by identifying the determinants of welfare in the urban and rural areas using OLS regressions and quantile regressions and secondly, by decomposing welfare inequality into the relative contributions of endowments and discrimination using the Oaxaca-Blinder [25,26]; decomposition method.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…To capture gender earning differences in rural Mozambique, we hypothesizing that female-headed households are disadvantaged in both income and food security, and therefore, female-headed households are more likely to be poor and food insecure than male-headed households as found elsewhere by [30,2].…”
Section: Hypothesized Drivers Of Household Food Insecuritymentioning
confidence: 99%